Freshwater ostracods (Crustacea) from Hainan Island, southern China, with description of a new species - Ma, Shunxin; Yu, Na (Zootaxa, 2020)
In this study, 24 non-marine ostracod species were found in 142 samples collected from diverse water bodies from Hainan Island, south China. Among them, a new species Pseudocypretta lineata n. sp. is described and illustrated. Twelve species are new records for China. Among them, six species are identified: Microdarwinula zimmeri (Menzel, 1916), Pseudocypretta lineata n. sp., Pseudostrandesia mamarilorum (Victor & Fernando, 1981c), Stenocypris malayica Victor & Fernando, 1981b, Stenocypris orientalis Victor & Fernando, 1981b and Strandesia freyi Victor & Fernando, 1981c. Six species are left in open nomenclature: Batucypretta sp., Candonopsis? sp., Cypridoidea gen. et sp. indet. 1, Cypridoidea gen. et sp. indet. 2, Cyprinotus cf. kimberleyensis McKenzie, 1966 and Vestalenula sp. Additionally, a re-description of Strandesia freyi is provided.